The four regions in settlement space: a game-theoretical approach to investment treaty arbitration. Part II: cases. (26th December 2017) - Broom, Mark; Collins, David; Hieu Vu, Trung; Thomas, Philip
Abstract: Following from Part I of this article, which introduced the notion of decision-modelling for investor–state arbitration, Part II of the article uses the game theoretic notions developed in Part I to explore the question of why a relatively large fraction of investor–state disputes proceed to arbitration tribunals. Likely explanations are advanced. The detailed mathematical model derived in Part I of the article is then used to analyse 31 cases where an investor–state dispute has been judged by an arbitration tribunal. Auxiliary mathematics are developed to identify the relevant averages and variances, which are then calculated from the full data set. Three sample cases are analysed in greater detail, with the model results being compared against the actual awards. It is concluded that applying the mathematical model of the international arbitration process developed in Part I together with the data analysis laid out in Part II will provide useful insight and guidance to both parties involved or likely to be involved in a dispute between investor and state.